Deceptive Manipulation of Competitive Starting Strategies Influences Subsequent Pacing, Physiological Status, and Perceptual Responses during Cycling Time Trials - Williams, Emily L.; Jones, Hollie S.; Sparks, S. Andy; Marchant, David C.; Midgley, Adrian W.; Bridge, Craig A.; McNaughton, Lars R. (Frontiers in Physiology, 2016)
Little is currently known regarding competitor influence on pacing at the start of an event and in particular the subsequent effect on the remaining distance. The purpose of the present study was to investigate the influence of starting pace on the physiological and psychological responses during cycling time trials (TT) utilising an innovative approach allowing pace to be accurately and dynamically replicated, as well as deceptively manipulated. Ten competitive male cyclists completed five 16.1 km TT, two baseline trials performed alone (BLs), and three with a simulated, dynamic avatar of which they were to match the pace of for the initial 4 km. The avatar represented either the cyclist’s fastest BL performance (NORM), 105% (FAST), or 95% (SLOW), of fastest BL performance (FBL). Physiological and psychological responses were measured every quartile of the TT. Despite manipulating a starting speed of ± 5% of fastest previous performance, there was no effect on overall 16.1 km TT performance. Manipulated starting strategies did however evoke different physiological and perceptual responses. Whole trial differences found that SLOW produced lower HR, VO2, BLa and RPE than FBL (p ≤ 0.03) and higher SE than FAST (p ≤ 0.03). Additionally, FAST had greater internal attention than NORM (p < 0.04). Over time all psychological and physiological variables had a significant condition x quartile interaction in the initial or second quartile mediated by the prescribed starting strategies. Furthermore, RPE, affect and internal attention remained elevated throughout FAST despite an attenuation in pace during self-selection of pace. There were no differences in performance time when manipulating a 16.1km cycling TT starting strategy. A slow start, encouraged greater positive perceptions, less negative physiological consequences than a faster start, and produces no impairment to performance time. It would therefore be considered an advantage in a non-drafting event, not to follow pace of fellow, superior competitors at the start of an event but perform a more negative pacing strategy, with the potential for a greater speed increase against opponents in the latter stages.